IDENTIFIKASI BAHAN TAMBAHAN MAKANAN BERBAHAYA (BORAKS, FORMALIN DAN RHODAMINE B) YANG ADA DI PASAR BATUJAJAR - Riayatul Haq, Reina; Nur fauziani, Ratu; Putri Ayudia, Syeikha; Nur Rahman, Syifa; Alfaruq, Galan; Dwi, Syalwa; Fatwa Azzahra, Shaffa (JURNAL KESEHATAN KARTIKA, 2023)
Background: Food additives (BTM) are ingredients/mixtures of ingredients which are not naturally part of the food raw materials, but are added to food to affect the nature or form of the food, including coloring agents, preservatives, flavoring agents, anti-clotting agents, bleaching agents and thickener. The results of the 2013 BPOM RI survey which tested a total of 24,906 food samples showed that 3,442 (13.82%) samples did not meet food safety and quality standards, including Borax 221 samples, Rhodamine B samples 304, Formalin samples 115, and Methanyl Yellow 9 samples. samples and Auramin 6 samples.2 It can be said that Indonesia is currently in a formalin and borax emergency. BPOM's analysis of 700 food samples collected in Java, South Sulawesi and Lampung in early 2016 showed 56% contained formaldehyde. madrasas in 30 cities in Indonesia. Of the 4,808 sample snacks collected, 1,705 (35.46%) samples did not meet the food safety and/or quality requirements (TMS). This study aims to analyze dangerous food additives (BTM) including Borax, Formalin and Rhodamine B in food sold at Batujajar Market. The samples used were purchased at the Batujajar market which consisted of 5 cilok, 5 salted fish and 5 crackers. Method: This research is a laboratory analytical research. The population in this study were cilok, salted fish and crackers sold in the Batujajar market. The samples for this study were instant cilok, raw salted fish and crackers that have a bright color, ripe and raw, which are sold in the Batujajar market. Result: The results of this study showed negative borax in 5 cilok samples, positive formalin in 2 of the 5 samples and negative rhodamine in all samples. Conclusion: It can be concluded that the cilok tested did not contain borax and the cracker samples tested did not contain rhodamine B but 2 samples of the salted fish tested contained formalin